The silence of counsellors and the attentive voice of listening - Davids, Nuraan (South African Journal of Higher Education, 2016)
We story our lives as we live it, and as story-telling beings, we are living and storying our lives in relation to others at once drawing from, and contributing to ongoing constructions of new stories. The telling and re-telling of our stories allows us a space in which we can make sense of who we are, and assign some meaning to our lives. Deciding what to do with our lives, and understanding how to reconcile who we are with what we do, or cannot do, is no longer a straightforward process directly linked to a specific job description. One can therefore appreciate Kobus Marees (ed.) Shaping the story: A guide to facilitating narrative career counselling (2011) as a valuable tool to navigate the work environments of clients in times of turbulence and transition. Picking up on the unstated value of our capacity as story-telling beings, Maree provides us with multiple ways of how the narrative, as a counselling methodology, provides clients with an opportunity to make decisions about career choices, while retaining a self. While in agreement with the numerous chapters contained in the book, and particularly with the dominant contention that the narrative constructed in career counselling is influenced by both the client and the counsellor, I am however, surprised by the silence of the voice of the counsellor, and Marees omission in assigning the same importance of the narrative to the counsellor as he has given to the client. To this end, in addition to offering a review of Marees book, I fill the silent gap of the counsellor with my own submission of his or her potential story and contribution to the narrative construction.